Application of Six Sigma in Quality Control Process at Indonesian Cement Company - Sudrajat, Darjat -; Saroso, Hardijanto; Lasmy, Lasmy; Herlina, Maria Grace; Syahchari, Dicky Hida (ExcelingTech, 2020)
An Indonesian Cement Company is facing the number of product’s defects in the packing process more than 200.000 bags or sacs annually. It is estimated to cause losses more than one billion rupiahs per year. Therefore, the Six Sigma method was proposed to solve this problem. This study was constitute a descriptive research; whereas based on its strategy, this study was constitute a case study; In addition based on time horizon, this study was constitute a longitudinal study. In the research used DMAIC processes, namely encompasses Define, Measure, Analyze, Improve and Control. The research’s results found that the existing process quality of cement packing in the company is out of control. So that the improvement process is needed by eliminating the causes of its. The main cause that must be a priority in its improvement is the machine (belt-conveyor) condition in the cement packing process. The main solution to prevent the occurrence of the main cause namely by checking the machine (belt-conveyor) before and after shift exchange by using a checksheet periodically. By implementing the Six Sigma method, it is hoped that the cement company can reduce or eliminate the existing waste estimated amount of one billion rupiah annually